2018
DOI: 10.1007/s10067-018-4141-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term etanercept retention patterns and factors associated with treatment discontinuation: a retrospective cohort study using Canadian claims-level data

Abstract: To examine 12-month retention rates over 6 years of etanercept patients in Canada, and to identify factors associated with treatment discontinuation. A retrospective cohort study was conducted using longitudinal prescription drug claims data from IQVIA Private Drug Plan database (PDP), Ontario Public Drug Plan database (OPDP), and Régie de l'assurance maladie du Québec database (RAMQ). Between 07/2008 and 06/2010, bio-naïve patients who initiated etanercept were identified and followed for 72 months. Twelve-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
1
18
1
Order By: Relevance
“…Previous research in the Canadian setting has shown that annual retention of ETN treatment among pediatric patients with a medical history consistent with JIA (94%) or ankylosing spondylitis (5%) ranges from 78% in year 1 to 80 to 90% over years 2–6, [7] suggesting therapeutic efficacy and tolerability. These levels of ETN treatment retention are higher than those reported by adult patients in the same setting over the same time periods [7, 8].…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Previous research in the Canadian setting has shown that annual retention of ETN treatment among pediatric patients with a medical history consistent with JIA (94%) or ankylosing spondylitis (5%) ranges from 78% in year 1 to 80 to 90% over years 2–6, [7] suggesting therapeutic efficacy and tolerability. These levels of ETN treatment retention are higher than those reported by adult patients in the same setting over the same time periods [7, 8].…”
Section: Introductionmentioning
confidence: 71%
“…Per privacy legislation in Quebec, a random sample drawn from the total RAMQ database was used in this study. These databases have been utilized previously in many studies evaluating the use of biologics and other medications in adult and pediatric patient populations [7, 8, 2529].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations